Жиһаз индустриясы үшін мамандар даярлаудағы инновациялық цифрлық шешімдер - Nurmakhanov Баймахан; Bukharbai Нұрғаным (Рroblems of engineering and professional education, 2024)
In the context of the rapid development of technologies and changing market requirements, this approach is becoming increasingly relevant, as it contributes to the formation of creative and innovative specialists. The purpose of the study is to analyze the use of digital design and design thinking in the educational process, as well as to assess their impact on the formation of professional competencies of students. The paper examines modern practices and methodologies, including the use of 3D modeling software, virtual reality and other digital tools that allow students to interact with real- time projects. The study used interactive multimedia tools, digital methods of graphic design, and virtual experiences adapted in the learning process. The results of the analysis show that the integration of digital technologies into training not only increases the level of student participation, but also contributes to the development of critical thinking, teamwork skills and the ability to solve practical problems in furniture design and production. These conclusions indicate the need to adapt educational programs to modern requirements and challenges, and also open up new opportunities for the use of innovative teaching methods in the furniture industry, which, in turn, can contribute to increasing the competitiveness of specialists in the labor market.